Native interaction across the frontier zone Of Hadrian's Wall - Trichler, P.K. (2016)
This dissertation will look at the transition from the Late Pre-Roman Iron Age through to the Roman period in what is today’s northern England and Scotland, specifically looking at the native communities and their interaction across and around the frontier of Hadrian’s Wall. It will compare the engagement of native peoples on either side of the frontier zone with each other and with the Romans occupying the Wall.